OVERVIEW OF THE MENTAL WORKLOAD OF FEMALE NURSES DURING THE COVID-19 PANDEMIC AT HOSPITAL X - Fatmawaty Mallapiang; Febriani Prastike; Nildawati Nildawati; Azriful Azriful (Homes Journal = Hospital Management Studies Journal, 2023)
In the Covid-19 pandemic crisis, nurses are professionals in the health sector who have to work and provide nursing services during the Covid-19 pandemic and always interact with patients who are positive for Covid-19 so as to increase the mental workload of nurses. The mental workload of nurses should be within normal limits. This study aims to describe the mental workload of female nurses during the Covid-19 pandemic. The type of research used is quantitative with a descriptive approach. The population in the study were all female nurses on duty at Hospital X with a total sample of 22 nurses using purposive sampling technique with inclusion criteria, namely female nurses in charge of handling Covid-19 and the ICU room. The results showed that the mental workload felt by female nurses was in the high category of 17 (77.3%) and very high category of 5 (22.7%). The mental workload of nurses is in the high category and the indicator of the NASA-TLX method is the most dominant on the mental workload of nurses in Hospital X, namely the time requirement indicator of 21.75%. Suggestions in this study are for nurses to manage their time as housewives and workloads and provide the best care during the Covid-19 pandemic.